IMPACT OF ACTIONAID UGANDA GENDER BASED VIOLENCE SHELTERS PROGRAM ON PROMOTION OF WOMEN RIGHTS: A CASSE OF KUMI MUNICIPALITY. - ELALU STEPHEN (My University, 2024)
The study examined the impact of ActionAid Uganda GBV shelters on the promotion of women rights in Kumi Municipality. The study objectives were; to assess the situation of violence against women and girls, to find out the effectiveness of GBV shelter interventions in the promotion of women rights, and to identify the challenges in the implementation of the programs associated to GBV shelters in Kumi Municipality. The study adopted a mixed research approach ie both qualitative and quantitative approaches; Study Population, the entity comprises of 228 respondents from which a sample size of 120 respondents was drawn. The findings revealed that GBV is still rampant in Kumi Municipality, the study further revealed that there was overwhelming demand for shelter services and yet the shelter cannot take onboard more than 5 people for accommodation. Among the challenges affecting the shelter were continued threats from the perpetrators against survivors housed at the shelter and lack of financial support to the survivors of GBV who wish to start new life and lack continued sensitization. In conclusion, it was observed that GBV is still rampant in Kumi Municipality and the major perpetrators are men and its therefore the duty of individuals, community members, government institutions, NGOs and stakeholders involved in promotion of human rights to stand up and be counted as the champions of human rights. The challenge affecting the shelter is limited source of funding, short life spun of the funding agencies. The study recommended that the LCs should be trained on handling GBV cases, local governments should plan to allocate funds towards shelter activities, Civil society Organizations should support victims of GBV, campaign channels should also be expanded and culprits of GBV against women should be apprehended through legal means.